MOOC de redação oficial em LibreOffice Writer - Bonorino, Liliane Silveira (2016)
This work was developed in the Program of Postgraduate Studies in Educational Technology Network, Professional Masters in Research Line Educational Development of Educational Technologies Network. The objective is to innovate in the provision of training mediated by Educational Technologies Network (ETN) through a MOOC (Massive Open Online Courses - Online Open Courses and Massive) for Moodle (Modular Object Oriented Dynamic Learning Enviroment). This research is justified by the fact that values training networking, promoting to the modality of Distance Education. To develop this work, it was adopt the research-action, resulting in the achievement of a vocational training via MOOC for improving the production of official documents in LibreOffice Writer. The product produced was Teaching Material for MOOC which was implemented in two phases: 1) module pilot in order to verify that the didactic and methodological organization of the course was well underway for the completion of the course; and, 2) MOOC, in order to promote not only training, but also the improvement of knowledge of the official texts in LibreOffice Writer. After analyzing the data collected in the pilot module, it was found that the teaching material and the strategy adopted to address the official writing in LibreOffice Writer were understood and were in accordance with the training needs of those involved. Analysis of the data obtained in the evaluation of research MOOC and its hypermedia courseware, realized that both provided the teaching-learning process mediated by educational technology network, in order to promote not only training, but also the improvement knowledge about the official writing in LibreOffice Writer. It was considered that the proposed objectives were included in the following measure: the "promote vocational training network through a MOOC writing of official documents in LibreOffice Writer, with hypermedia courseware" successful, since training was promoted network considered by course participants as excellent; 2) to "disseminate and encourage the integration of LibreOffice Writer to professional practices" has been satisfactorily met, since the course participants have expressed interest in joining this program to their practices; and 3) to "explore the potential of LibreOffice Writer to produce texts by hypermedia courseware" it was successful, as the course participants considered it great. Therefore, MOOC, it expands the supply of training mediated educational technology network, which, in addition to enabling access to a large number of participants, is a potentiating tool, through the practice of freedom, innovation vocational training network.